Photoswitchable precision glycooligomers and their lectin binding - Ponader, Daniela; Igde, Sinaida; Wehle, Marko; Märker, Katharina; Santer, Mark; Bléger, David; Hartmann, Laura (Beilstein Journal of Organic Chemistry, 2014)
The synthesis of photoswitchable glycooligomers is presented by applying solid-phase polymer synthesis and functional building blocks. The obtained glycoligands are monodisperse and present azobenzene moieties as well as sugar ligands at defined positions within the oligomeric backbone and side chains, respectively. We show that the combination of molecular precision together with the photoswitchable properties of the azobenzene unit allows for the photosensitive control of glycoligand binding to protein receptors. These stimuli-sensitive glycoligands promote the understanding of multivalent binding and will be further developed as novel biosensors.
Keywords: azobenzene; glycopolymer; lectin binding; multivalency; multivalent glycosystems; photoswitch; precision polymer